2021
DOI: 10.3390/curroncol28020121
|View full text |Cite
|
Sign up to set email alerts
|

PTEN R130Q Papillary Tumor of the Pineal Region (PTPR) with Chromosome 10 Loss Successfully Treated with Everolimus: A Case Report

Abstract: Papillary tumors of the pineal region (PTPR) can be observed among adults with poor prognosis and high recurrence rates. Standards of therapy involve total surgical excision along with radiation therapy, with no promising prospects for primary adjuvant chemotherapy, as long-term treatment options have not been explored. Chromosome 10 loss is characteristic of PTPR, and PTEN gene alterations are frequently encountered in a wide range of human cancers and may be treated with mTORC1 inhibitors such as everolimus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The chromosomal microarray of the resected tumor was arguably the most helpful study, as it demonstrated the loss of chromosomes 10 and X, and the gain of material on chromosomes 8, 9, and 12. Previous molecular studies have shown the loss of chromosome 10 in 75% of cases of PTPRs, making this feature characteristic of this type of tumor [5]. Additionally, the pattern of genomic alterations present in our patient's tumor has been reported in prior cases of PTPR and would be an unusual finding for other primary pineal region masses, including pineoblastoma, ependymomas, and primary CNS tumors [6].…”
Section: Cam52 On Tumor Cells With B) Patchy Positivity For S100 On T...supporting
confidence: 69%
“…The chromosomal microarray of the resected tumor was arguably the most helpful study, as it demonstrated the loss of chromosomes 10 and X, and the gain of material on chromosomes 8, 9, and 12. Previous molecular studies have shown the loss of chromosome 10 in 75% of cases of PTPRs, making this feature characteristic of this type of tumor [5]. Additionally, the pattern of genomic alterations present in our patient's tumor has been reported in prior cases of PTPR and would be an unusual finding for other primary pineal region masses, including pineoblastoma, ependymomas, and primary CNS tumors [6].…”
Section: Cam52 On Tumor Cells With B) Patchy Positivity For S100 On T...supporting
confidence: 69%